SOCIAL CHARACTERISTICS AND CONFORMITY OF BASKETBALL PLAYERS - Igor Vučković; Aleksandar Gadžić; Željko Sekulić; Duško Lepir (Exercise and Quality of Life)
The subject of present research was relations between basketball playersí social characteristics and their conformity toward coach and club management. Study aim was to explore the relationship between basketball playersí social characteristics and their conformity toward coach and club management. Sample of examinees was consisted of 113 adult basketball players. Research instruments were modified social questionnaire SSMAXIP (Hoöek, 2004), and modified conformity scale (The Conformity Scale, Mehrabian, & Stefl, 1995). Internal reliability of the conformity scale was ·=.74. Spearmanís coefficient of rank correlation was used in order to examine significance of relations between social characteristics and conformity of basketball players. This analysis has shown that significant relationships between the majority of social characteristics and conformity toward coach and club management of basketball players do not exist, indicating that some outer factors contribute to playersí high conformity.